A tale of two pregnancies: A Critical Interpretive Synthesis of women's perceptions about delayed initiation of antenatal care. Issue 3 (June 2018) - Haddrill, Rosalind; Jones, Georgina L.; Anumba, Dilly; Mitchell, Caroline
Abstract: Background: Delayed access to antenatal care in high income countries is associated with poor maternal, fetal and neonatal outcomes. The aim was to synthesise the diverse body of evidence around women's views of early antenatal care and barriers to attendance in such countries. Critical Interpretive Synthesis integrates the process of systematic review with the qualitative methods of meta-ethnography and grounded theory, with a focus on theory generation to inform policy, practice and future research. Methods: Database searches were conducted, supplemented with reference and citation tracking and website searching between February 2014 and April 2016. Qualitative data analysis methods were used to extract and summarise the key themes from each study. A taxonomy of constructs was created, with the synthesis developed to thread these together. Fifty-four papers were synthesised, including qualitative, quantitative, mixed method and systematic review, published between 1987 and 2016. Findings: Seventeen constructs around the core concept of 'acceptance of personal and public pregnancies' were produced. Acceptance of the 'personal' pregnancy considers the contribution of mindset in the recognition and acceptance of pregnancy, influenced by knowledge of pregnancy symptoms, pregnancy planning and desire. Acceptance of the 'public' pregnancy considers women's assessment of the social consequences of pregnancy, and the relevance and priority of antenatal care. Conclusion: Critical Interpretive Synthesis offers a systematic yet creative approach to the synthesis of diverse evidence. The findings offer new perspectives on women's perceptions of early pregnancy and attendance for care, which may be used to facilitate timely antenatal provision for all pregnant women.